AKAD MUDHARABAH DAN MURABAHAH DALAM PERBANKAN SYARIAH; ‎TINJAUAN FILSAFAT HUKUM - Almas'udah Almas'udah (Al Hikmah: Jurnal Studi Keislaman, 2017)
Islamic banks are banks that carry out business activities based on Sharia principles, namely agreement rules based on Islamic law between banks and other parties to deposit funds and or finance business activities, or other activities stated in accordance with Sharia. In running its business, Islamic banks use a profit sharing pattern which is the main foundation in all its operations. In Islamic Banking, basically eliminating interest as an element of prudence in the context of compliance with sharia, for this reason the Sharia Bank applies the principle of profit sharing and is spawned in contracts at Islamic banks, and this article will discuss the Murabahah and Mudarabah agreements in Sharia Sharia Indonesia and how Murabahah and Mudarabah contracts in legal philosophy review. Although the growth of the Islamic banking industry in Indonesia is greater than conventional banking, there are many challenges that must be considered and resolved to ensure the sustainability of growth and development of Islamic banking in the future. There is a difference in concept between Islamic banking and conventional banking. In conventional banking there are two agreements. First, the agreement between the bank and the customer, and get a certain percentage of bank interest. Second, the agreement between the Bank and the borrower, and has the right to get a certain percentage of the interests of the borrower. The Bank's profit comes from taking the interest rate difference offered to the customer at an interest rate charged to the borrower.